Recent Advances in Molecular, Multimodal and Theranostic Ultrasound Imaging - Kiessling, Fabian (2013)
Ultrasound (US) imaging is an exquisite tool for the non-invasive and real-time diagnosis of many different diseases. In this context, US contrast agents can improve lesion delineation, characterization and therapy response evaluation. US contrast agents are usually micrometer-sized gas bubbles, stabilized with soft or hard shells. By conjugating antibodies to the microbubble (MB) surface, and by incorporating diagnostic agents, drugs or nucleic acids into or onto the MB shell, molecular, multimodal and theranostic MB can be generated. We here summarize recent advances in molecular, multimodal and theranostic US imaging, and introduce concepts how such advanced MB can be generated, applied and imaged. Examples are given for their use to image and treat oncological, cardiovascular and neurological diseases. Furthermore, we discuss for which therapeutic entities incorporation into (or conjugation to) MB is meaningful, and how US-mediated MB destruction can increase their extravasation, penetration, internalization and efficacy.